Two and Five Year Plan of Bilaspur State - Planning Commission (Planning Commission, 1955)
Bilaspur is a small unit, 453 square miles in area with a population of 1,30,000. It is situated in the outer hills of the Himalayas bordering on the plains. The river Sutlej and its tributaries form the drainage system of this State and along with the ranges of hills divide it into a number of valleys and dales. The main hill ranges number 7 and as many are the tributaries of the river. The river passes right across the middle of the State and divides it into two almost equal parts.
Administration of Bilaspur